(untitled) (Web of Teachers: Inderscience Research, 2025)
Iron deficiency anemia is one of the important factors in the course of pneumonia in children. Iron deficiency leads to a lack of hemoglobin in the body, which is responsible for transporting oxygen. Due to this, the respiratory process is disrupted, the normal functioning of the respiratory tract and lung tissue deteriorates. As a result, the course of such severe diseases as pneumonia is complicated, its duration increases, and the likelihood of complications increases. This condition is especially serious in infants and young children, since their immune system will not be fully formed yet, and the defense mechanisms are considered weak.